Upaya Pengentasan Kemiskinan dengan Mengurangi Konsumsi Rokok di Indonesia - Memi Almizi; Istiana Hermawati (Balai Besar Litbang Pelayanan Kesejahteraan Sosial, 2018)
Poverty is a general problem that should be seriously handled by the government. The second of the biggest poverty contributions in Indonesia is the cigarette smoking consumption. The purpose of this research is to analyze the connection between poverty and cigarette smoking consumption and the effetcs that are caused by that connection itself also what efforts that should be needed to alleviate the poverty by reducing the consumption of cigarettes. This research uses descriptive qualitative approach with libraries study type. The data sources of this study are from statistical data, newspaper, and results of the research literature. The second determinant poverty is cigarettes. The facts show that cigarette smoking consumption gives a bad impact both in health and economic so that people are contracted in the circle of poverty. Poverty reduction is an action that both the goverment and the society should be responsible about.Â The recommendations that are given to the Government; 1. The Directorate General of taxation and customs needs to have the price of cigarettes highly increased; 2. The Ministry of finance and state budget planning needs to recalculate the budgeting for health and the customs revenue of the cigerette itself. 3. Social Ministry needs to provide the oversight on the peple as the social aid recipient through the Indonesian Conditional Cash Transfer Programme that the aid is to be productively used and Social Ministry needs to do the socialization and to create the new rules as well that the social aid recipient should be those who are not cigerette smokers.